MOORA Method Analysis For Decision Support System Determining the Best Subsidized Housing in Tanjung Morawa - Marpaung, Preddy; Suci Amalia Sari; Fadya Larasati; Pasaribu, Sutrisno Arianto (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Subsidized housing is a government program as an alternative for low-income communities so that the primary needs of the community such as housing are met, especially for people who are already married. One of the areas where subsidized housing is located is the Tanjung Morawa area, Deli Serdang, North Sumatra. However, the problem for the community or employees who want to find a residence to live in the Tanjung Merowa area is the difficulty in determining a subsidized house that suits their wishes, such as comfort, housing price, house model, strategic location. The factor that makes it difficult for people to determine a residential house is because there is no knowledge or information about which subsidized house is the best according to the criteria to be occupied. Therefore, it is necessary to apply a method to analyze to determine the best subsidized house, the Objective Optimization on the basis of Ratio Analysis Simple (MOORA) method is applied to analyze the decision support system to determine the best subsidized house in Tanjung Morawa, where the MOORA method is able to produce the best subsidized house based on the highest value or ranking, where the highest value is ranking 1 alternative 6, Mulia Residence housing.